Embodied Homo Sacer in Mahasweta Devi's "Draupadi" - Sharma, Pradip (Humanities and Social Sciences Journal, 2022)
Foucauldian biopolitics ultimately turns into necropolitics when the regime incorporates state racism. This article analyzes the process of dehumanization of the homo sacer in Mahasweta Devi's story, "Draupadi" which entails the Naxalites Movement of India at the background and the state's hard power deployment to deter it. It excavates how the all caring biopolitical regime wields terror, exile, and imposes rampant killing over the penury-laden subalterns in Birbhum India. While resisting the death in life Dulna is killed and Dopdi is sieged, incarcerated, disrobed, mangled, and finally raped with impunity which replicates the ordeal of the Muselmann in Nazi Camp. The story flays the paradox of welfarism for the elite not for the poor in azad India. This article aims at the suspension of law and imposition of legal terror over the dalits. While probing into the unequal social praxis, and state sponsored bioviolence, Mahasweta's Draupadi dramatizes the stark outlawry and violence over subaltern homo sacer.